THE WAY OF THE SPIRIT - A JAIN JOURNEY: STUDIES IN JAINA SPIRITUALITY - Sekha, Vincent (Journal of Dharma, 1988)
Spirituality has been defined severally by several people dependingupon diverse contexts. In a general sense, spirituality is primarily, the Spirit. It is the movement of the spirit and its work. It is the life that is lived in the awareness of the indwelling and all-pervading spirit, coupled with all-round detachment and continuous transcendence till the realization of the ultimate goal.